Disability Representation in J. Albert Mann’s The Degenerates - Soha Mohamed Essawi (International Journal of Instructional Technology and Educational Studies)
This paper aims to show how disability is represented in J. Albert Mann’s The Degenerates (2020). It highlights the issues encountered by individuals with disabilities and the role of society in reinforcing negative ideas about people with disabilities. Mann’s The Degenerates criticizes the sterile mindset embraced by society and the norms commonly accepted by society that define ableism/ disability. In addition, it addresses important issues such as "societal perception," "normalcy and perfection," "stigmatization," "ableism," "eugenics," "distorted self-perception," "marginalization and exclusion," and "resistance." The analysis reflects the effect of society’s crooked malpractices towards people with disabilities. Keywords: disability, disability fiction, normalcy, stigmatization, ableism, resistance, and narration.This paper aims to show how disability is represented in J. Albert Mann’s The Degenerates (2020). It highlights the issues encountered by individuals with disabilities and the role of society in reinforcing negative ideas about people with disabilities. Mann’s The Degenerates criticizes the sterile mindset embraced by society and the norms commonly accepted by society that define ableism/ disability. In addition, it addresses important issues such as "societal perception," "normalcy and perfection," "stigmatization," "ableism," "eugenics," "distorted self-perception," "marginalization and exclusion," and "resistance." The analysis reflects the effect of society’s crooked malpractices towards people with disabilities. Keywords: disability, disability fiction, normalcy, stigmatization, ableism, resistance, and narration.